Role of Remdesivir therapy in COVID-19 patients: a systematic review and meta-analysis - Srikumar, Shabarini; Muthiah, Aravind; Perumal, Shridharan (International Journal of Research in Medical Sciences, 2022)
The rapid global spread of corona virus disease has created an adversity for the scientific community in managing the disease with appropriate therapeutic measures. The use of remdesivir was initiated as an experimental drug and the later studies analyzing its efficacy showed mixed results. In this meta-analysis, we systematically review the efficacy and safety of remdesivir for the treatment and prevention of COVID-19. A systematic search of databases such as Pubmed, Lancet, Medline, Google Scholar, Cochrane, Embase was carried out through which 1451 articles were identified. 8 articles among it were finally taken for the meta-analysis after several stages of exclusion, to improve the quality and accuracy of the results, out of which the results of 4 studies were in favour of the efficacy of remdesivir, while other 4 studies were against the efficacy of remdesivir. The total sample size is 12,028. The result of our statistical analysis was that OR=0.965 (95% CI; 0.6633 to 1.47) for the effect of remdesivir on mortality reduction in COVID-19 patients. Remdesivir therapy for COVID-19 did not show reduced time to clinical recovery or improved mortality rate. Other outcomes of study like requirement of oxygen support, easier weaning off of mechanical ventilation were also not significantly improved with administration of remdesivir in critically ill COVID-19 patients.